Cinnamon: Mystic Powers of Minute Ingredient - Pallavi Kawatra; Rathai Rajagopalan (Pharmacognosy Research, 2015)
Cinnamon, due to its exotic flavor and aroma, is a key ingredient in the kitchen of every household. From the beginning of its use in 2800 BC by our ancestors for various purposes such as anointment, embalming and various ailments, it has instigated the interest of many researchers. Recently many trials have explored the beneficial effects of cinnamon in Parkinsons, diabetes, blood, and brain. After extensive research on PubMed and Google scholar, data were collected regarding its antioxidant, anti‑inflammatory, antilipemic, antidiabetic, antimicrobial, and anticancer effect. This systematic review underlines the surplus health benefits of this clandestine ingredient and the scope of further research in these clinical scenarios.
Keywords: Blood; Cinnamon; Diabetes; Parkinsons